2022
DOI: 10.1021/acs.cgd.2c00320
|View full text |Cite
|
Sign up to set email alerts
|

Zn(II) Complexes Based on a Schiff Base: Mechanochromism- and Solvent Molecule-Dependent Acidochromism

Abstract: A new Schiff base molecule (HL) with a triphenylamine group and its three zinc(II) complexes (1, 1-THF, and 1-DMF) were synthesized and characterized. As expected, three kinds of loosely packed structures that are susceptible to mechanical stimulation were adjusted through twisted conformations and weak intermolecular interactions (C−H•••π, π•••π, and hydrogen bonds). They all exhibit remarkable mechanochromic luminescence (MCL) behavior with high contrast upon mechanical grinding due to the phase transition b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In summary, the variegated vapochromic response of the cast films of 1 (Scheme ) represents a unique feature in the panorama of stimuli-responsive Zn­(II) molecular materials. , In fact, the possibility to detect various VOCs having Lewis basicity, and in particular, the discrimination of primary aliphatic amines and pyridine, represents a clear advance compared to our previous work , and to other vapochromic investigations, the latter mostly related to acidochromism. …”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…In summary, the variegated vapochromic response of the cast films of 1 (Scheme ) represents a unique feature in the panorama of stimuli-responsive Zn­(II) molecular materials. , In fact, the possibility to detect various VOCs having Lewis basicity, and in particular, the discrimination of primary aliphatic amines and pyridine, represents a clear advance compared to our previous work , and to other vapochromic investigations, the latter mostly related to acidochromism. …”
Section: Resultsmentioning
confidence: 72%
“…To further explore the responsive behavior of Zn(salen)type molecular materials toward volatile Lewis bases, we chose the Zn(salmal) derivative, 1, having the 5,5′-tert-butyl-bulky substituent on the salicylidene rings, allowing comparison with previous investigated complexes 27 −29,31 having different substituents and substitution patterns. This complex was found to possess unique thermochromic and vapochromic characteristics, compared to those of our previous investigations 29,31 and literature studies on stimuli-responsive molecular materials of Zn(II) coordination complexes, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]30 allowing the detection of various VOCs having Lewis basicity and, among them, the discrimination of primary aliphatic amines and pyridine.…”
Section: ■ Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…7,9,22–43 In addition, vapochromic luminescence is also an important type of stimulus response to certain vapors. 44–51 Among vapochromic properties, the responses to HCl vapor and NH 3 vapor are of particular importance because they are generated in electroplating, textile, fertilizer production, and rubber industries. Inhalation of HCl vapor can lead to respiratory ulcers and pulmonary edema, while excessive exposure to NH 3 vapor can cause corrosion of the skin, eyes, and respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc( ii ) and cadmium( ii ) complexes establish one of the most important classes of emissive compounds. 71–121 Earlier, we synthesized a series of mononuclear zinc( ii ) and cadmium( ii ) complexes with hybrid ligands containing a 2,2′-bipyridine moiety and natural terpene (+)-limonene or (+)-3-carene moieties and demonstrated that they exhibit luminescence with the quantum yield increasing in the following order: free ligand < cadmium( ii ) complex < zinc( ii ) complex. 122 The complexes with the limonene derivative demonstrate excitation wavelength–dependent emission with nanosecond and microsecond lifetimes of the excited states.…”
Section: Introductionmentioning
confidence: 99%